Evaluation of the effect of the type of hysterectomy on the incidence of stress urinary incontinence - Biegańska, Oliwia; Biczak, Emilia; Przywara, Grzegorz; Jagodziński, Adam; Wlaźlak, Edyta; Murawski, Marek (Menopause Review/Przegląd Menopauzalny, 2025)
Hysterectomy is performed by various surgical methods: abdominal, vaginal, laparoscopic, or robotic, and with different extents: supracervical, total, or radical. Scientific reports indicate that hysterectomy is a risk factor for stress urinary incontinence (SUI). The aim of this paper is to review scientific studies on the effect of the type of hysterectomy on the incidence of SUI. Original open-access articles in English language available in the PubMed, Google Scholar, and ScienceDirect databases published in the period 2004–2024 were included. Studies suggest the following: vaginal hysterectomy is associated with a higher risk of SUI than abdominal hysterectomy; abdominal hysterectomy is associated with a higher risk of SUI than laparoscopic hysterectomy; and it is likely that supracervical hysterectomy is associated with a higher risk of SUI than total hysterectomy; however, some scientific reports do not show significant differences in SUI between the above types of hysterectomy, so the first 3 conclusions should be approached with caution; it is uncertain whether the removal of the adnexa during hysterectomy increases the risk of SUI; and there were no differences between traditional laparoscopic hysterectomy and robotic-assisted laparoscopic hysterectomy. More good-quality studies on the effect of the type of hysterectomy on the incidence of SUI are necessary.